1984
DOI: 10.1002/jez.1402320333
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic hormones, insulin/glucagon molar ratios, and somatostatin as determinants of avian carbohydrate metabolism

Abstract: The endocrine pancreas of birds contains cell populations similar, if not identical, to those found in mammalian pancreata, although the topographical distributions of these cell types differ to some extent. Insulin-secreting (B) cells, glucagon-secreting (A) cells, somatostatin-secreting (D) cells, and pancreatic polypeptide-secreting (PP or F) cells are distributed unequally among the four pancreatic lobes, with most of the A cells located in the third and splenic lobes and PP cells residing in both islet ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 4 publications
1
34
0
3
Order By: Relevance
“…In mammals and birds, glucose homeostasis during fasting is predominantly controlled by interactions between insulin and glucagon, with decreasing I/G ratios associated with increased substrate mobilization and stimulation of gluconeogenesis (Cuendet et al, 1975;Hazelwood 1984). Observations in weaned elephant seal pups suggest that declining I/G ratios while fasting result from increased glucagon levels coupled with either declining or stable insulin levels (Ortiz et al, 2003;Champagne et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals and birds, glucose homeostasis during fasting is predominantly controlled by interactions between insulin and glucagon, with decreasing I/G ratios associated with increased substrate mobilization and stimulation of gluconeogenesis (Cuendet et al, 1975;Hazelwood 1984). Observations in weaned elephant seal pups suggest that declining I/G ratios while fasting result from increased glucagon levels coupled with either declining or stable insulin levels (Ortiz et al, 2003;Champagne et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin inhibits the release of all pancreatic hormones with the greatest inhibitory effect being against glucagon. It has least effect on PP secretion (Hazelwood, 1984). The Houbara pancreatic islet also contains NPY immunoreactive cells which as in other avian species occur only in neuronal structures of the pancreas (ElSalhy et al 1987) and mammals (Su et al 1987 ;De Giorgio et al 1992).…”
Section: mentioning
confidence: 98%
“…In addition, not only did PP and glucagon not exhibit a reciprocal distribution as observed in the chicken pancreas (Tomita et al 1985), but 20 % of glucagon immunoreactive cells also contained PP. Whilst glucagon is recognised as a major pancreatic hormone involved in glucoregulation in birds (Epple et al 1980 ;Falkmer & Van Noorden, 1983 ;Hazelwood, 1984), the dominant factor in homeostasis is the insulin\glucagon (I\G) ratio. The I\G ratio of 1n8-2n2 established in birds suggests that birds are normally in a catabolic mode.…”
Section: mentioning
confidence: 99%
“…AGE -advanced glycation end product BB -BioBreeding CAM -chorioallantoic membrane DMEM -Dulbecco's modified Eagle's medium FCS -fetal calf serum FPG -fasting plasma glucose GK -Goto Kakizaki HH6 -head-fold stage NOD -non-obese diabetic PG -plasma glucose ROS -reactive oxygen species STZ -streptozotocin normal to high levels of insulin, high glucagon levels, and insulin resistance in birds has indicated similarities between their normal condition and maturity onset diabetes in man [19]. The majority of reported cases of avian diabetes have occurred in small birds such as the parakeet and canary [18].…”
Section: Abbreviationsmentioning
confidence: 99%
“…The A and mammalian type islets are almost exclusively confined to the splenic and third lobes, whereas B islets are distributed throughout all the lobes of the pancreas [40,41]. High levels of normal blood glucose in birds and insufficient insulin response to glucose by islets from 4-to 6-week-old chicks have been reported [19]. However, our blood glucose measurements in embryonic chicks up to 15 days after hatching [12], and previous studies on metabolic hormone profile in embryonic and posthatch chicks [42], have shown a gradual increase in blood glucose levels [9,43,44].…”
Section: Usability Of Chick Pancreatic Islets To Screen For Insulin Smentioning
confidence: 99%